SUPPLY LOGISTICS FOR IMPROVEMENT OF IRON AND STEEL ENTERPRISES - S. Shakeev (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
This article describes the techniques that help to improve the material and technical supply management of allied industries. Resource endowment of Kazakhmys Corporation had been analyzed. To control physical resources effectively logistics center establishment for allied mining enterprises was offered.